Key Performance Processes in Islamic Hospitals: A Maslahah-Based Analytical Network Process Approach - Saputro, Eko Hadi; Firdaus, Achmad (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study adopts the Analytic Network Process (ANP) approach, integrating the MUKISI Certification Standards and DSN-MUI Fatwa No. 107 of 2016 to develop key processes based on Maslahah Performa (MaP) in Islamic Hospitals (IH). A qualitative research methodology was employed, utilizing interviews, questionnaires, documentation, and literature reviews to collect data from academics, experts, and practitioners. The results indicate that worship orientation is the highest priority in key processes , with a score of 0.230, followed by internal process orientation,talent, learning, customer, and wealth, each with a score of 0.153. These findings underscore the critical role of integrating spiritual values into IH governance to enhance competitive advantage, deliver comprehensive healthcare services, and contribute to the strengthening of the halal ecosystem in the healthcare sector. The implications of this model are expected to provide practical guidance for improving the sustainable performance of IH. Additionally, it offers a foundation for further academic research aimed at developing more comprehensive studies in this field.